"Ag-Gag" Laws: Evolution, Resurgence, and Public Health Implications. (February 2019) - Ceryes, Caitlin A.; Heaney, Christopher D.
The term "ag-gag" refers to state laws that intentionally limit public access to information about agricultural production practices, particularly livestock production. Originally created in the 1990s, these laws have recently experienced a resurgence in state legislatures. We discuss the recent history of ag-gag laws in the United States and question whether such ag-gag laws create a "chilling effect" on reporting and investigation of occupational health, community health, and food safety concerns related to industrial food animal production. We conclude with a discussion of the role of environmental and occupational health professionals to encourage critical evaluation of how ag-gag laws might influence the health, safety, and interests of day-to-day agricultural laborers and the public living proximal to industrial food animal production.